2020
DOI: 10.1016/j.bonr.2020.100713
|View full text |Cite
|
Sign up to set email alerts
|

Bone phenotype in melanocortin 2 receptor-deficient mice

Abstract: Considering that stress condition associated with osteoporosis, the hypothalamic-pituitary-adrenal (HPA) axis, which is essential for central stress response system, is implicated in regulating bone mass accrual. Melanocortin 2 receptor (MC2R), the receptor of adrenocorticotropic hormone is expressed in both adrenal gland cells and bone cells. To elucidate the role of HPA axis in bone metabolism, we assessed the skeletal phenotype of MC2R deficient mice ( MC2R −/− mice).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Our qPCR result demonstrated that deletion efficiency of Tfr1 gene, Tfrc , in vertebra is less than femurs ( Figure 2—figure supplement 9 ). It is also likely that the different physical properties, remodeling rate, microenvironment, and the heterogeneous osteoclast subtypes in the distinct sites and compartments of bone may contribute to these site- and compartment-specific phenotypes which have been reported in other genetically modified mouse models ( Cruz Grecco Teixeira et al, 2016 and Sato et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our qPCR result demonstrated that deletion efficiency of Tfr1 gene, Tfrc , in vertebra is less than femurs ( Figure 2—figure supplement 9 ). It is also likely that the different physical properties, remodeling rate, microenvironment, and the heterogeneous osteoclast subtypes in the distinct sites and compartments of bone may contribute to these site- and compartment-specific phenotypes which have been reported in other genetically modified mouse models ( Cruz Grecco Teixeira et al, 2016 and Sato et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various melanocortin receptors are expressed in bone cells, and activation of melanocortin receptors can cause increased proliferation and expression of a variety of genes in osteoblastic cells (19). In MC2R -/-mice, bone mineral density as well as the thickness of the cortical bone of femur increased (20). Because the FGD1 patients had excess ACTH even after cortisol treatment, activation of other melanocortin receptors in bone cells may account for their tall stature.…”
Section: Discussionmentioning
confidence: 99%
“…This observation may, to some extent, suggest that MC2R does not affect height through the activation of growth hormone/insulin-like growth factor-1 axis. A mouse model of MC2R-deficient (MC2R −/− ) mice displayed abnormal bone metabolism, but no growth abnormality was observed [Sato et al, 2020]. B6N5 generations of MC2R −/− mice showed normal development and function of reproductive organs but did not grow abnormally [Chida et al, 2009].…”
Section: Discussionmentioning
confidence: 99%